Ill met by murder [large type] - Duncan, Elizabeth J. (Duncan, Elizabeth J. Shakespeare in the Catskills mysteries., 2017)
"Costume designer Charlotte Fairfax is enlisted by theater company supporter Paula Van Dusen to investigate the murder of a family friend who happens to be a business rival of her daughter's fiancé and throws herself into an investigation of shady business deals, a missing dog, and long buried family secrets"--